Unraveling the Role of Acetic Acid Bacteria Comparing Two Acetification Profiles From Natural Raw Materials: A Quantitative Approach in Komagataeibacter europaeus - Román-Camacho, Juan J.; Mauricio, Juan C.; Santos-Dueñas, Inés M.; García-Martínez, Teresa; García-García, Isidoro (Frontiers in Microbiology, 2022)
The industrial production of vinegar is carried out by the activity of a complex microbiota of acetic acid bacteria working, mainly, within bioreactors providing a quite specific and hard environment. The ‘omics’ sciences can facilitate the identification and characterization analyses of these microbial communities, most of which are difficult to cultivate by traditional methods, outside their natural medium. In this work, two acetification profiles coming from the same acetic acid bacteria starter culture but using two natural raw materials of different alcoholic origins (fine wine and craft beer), were characterized and compared; it is aimed thus emphasize in the study of the effect of these raw materials. For this purpose, the composition and natural behavior of the microbiota present throughout these profiles were analyzed by metaproteomics, focusing, mainly, on the quantitative protein profile of Komagataeibacter europaeus; this species provided a protein fraction significantly higher (73.5%) than the rest one. A submerged culture system and semi-continuous operating mode were employed for the acetification profiles and liquid chromatography with tandem mass spectrometry (LC-MS/MS) for the protein analyses. The results showed that neither of two raw materials modified barely the microbiota composition of the profiles, however, they had an effect on the protein expression changes in different biological process. A molecular strategy in which K. europaeus would prevail over other species by taking advantage of the different features offered by each raw material has been suggested; first, by assimilating the excess of inner acetic acid through the TCA cycle and supplying biosynthetic precursors to replenish the cellular material losses; second, by a previous assimilation of the excess of available glucose, mainly in the beer medium, through the glycolysis and the pentose phosphate pathway; third, by triggering membrane mechanisms dependent on proton motive force to detoxify the cell at the final moments of acetification. This study could complement the current knowledge of these bacteria as well as to expand the use of diverse raw materials and optimize operating conditions to obtain quality vinegars.